2020
DOI: 10.1371/journal.pone.0239901
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting and optimizing Agrobacterium-mediated genetic transformation via ensemble model- fruit fly optimization algorithm: A data mining approach using chrysanthemum databases

Abstract: Optimizing the gene transformation factors can be considered as the first and foremost step in successful genetic engineering and genome editing studies. However, it is usually difficult to achieve an optimized gene transformation protocol due to the cost and time-consuming as well as the complexity of this process. Therefore, it is necessary to use a novel computational approach such as machine learning models for analyzing gene transformation data. In the current study, three individual machine learning mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 81 publications
1
31
0
Order By: Relevance
“…Recently, different machine learning algorithms have been successfully utilized to predict and optimize various plant physiological processes. Several studies [24,58,63] used MLP to predict various plant biological processes. However, they only applied the MLP model and did not compare this well-known algorithm with other models.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, different machine learning algorithms have been successfully utilized to predict and optimize various plant physiological processes. Several studies [24,58,63] used MLP to predict various plant biological processes. However, they only applied the MLP model and did not compare this well-known algorithm with other models.…”
Section: Plos Onementioning
confidence: 99%
“…Hence, there is a serious need to use nonlinear statistical methodology such as artificial neural networks (ANNs). The reliability and accuracy of different ANNs such as Radial basis function (RBF), Multilayer Perceptron (MLP), and Generalized Regression Neural Network (GRNN) have been previously proven in different fields of science and technology such as in vitro culture, prediction of microRNAs and transcription factors (TFs), analysis of plant promoters, remote sensing studies, genome prediction, and phenomics studies [24][25][26][27]. ANNs are a type of nonlinear computational methods, which is applied for different aims such as clustering, predicting, and classifying the complex systems [28].…”
Section: Introductionmentioning
confidence: 99%
“…Artificial intelligence (AI) is applied to address matters that cannot be clarified by traditional computational methods. Artificial neural networks (ANNs) are one of the main parts of AI discovering complex nonlinear relationships amongst input and output data [7,13,[24][25][26][27][28][29][30]. Indeed, ANNs are brain-inspired systems that emulate human brain capability of sensing and thinking, in a simplified way, to processes information and identify patterns [31].…”
mentioning
confidence: 99%
“…[ 53 ]. Therefore, ensemble algorithms were built to improve robustness over a single model with combining the predictions of several models [ 54 , 55 ]. In this study, the predictions derived from the RF, RBF, and SVM algorithms were used to build an ensemble model based on the bagging method.…”
Section: Discussionmentioning
confidence: 99%
“…F-measure is known as a reliable parameter that can be used to evaluate efficiency and accuracy of ML algorithms [ 19 ]. Recent studies have reported the success of using stochastic gradient boosting and E-B modeling in plant science [ 19 , 55 ], but not in the computational component of the plant genome editing. The E-B model exhibited the highest off-target prediction performance (AUC-ROC of 0.74 and AUC-PRC of 0.71) based on MIT and CFD scores.…”
Section: Discussionmentioning
confidence: 99%